Identificación y control de alga verde patogena en almacigos de tabaco (Nicotina tabacum) var. Habano Nicaragua en Juan Guerra-San Martín - Águila Cenepo, Omer Del (2000)
With the aim of identifying and! green algae and pathogenic possible to find a method of chemical management to reduce the harmful effect on seedlings of Nicotiana tabacum. black variety, this research was conducted between January to March 2000 in the Juan Guerra District, in the San Martin region located at a latitude south of 061130 'west longitude 76030' to 232 m. s. n. m, at the premises of the tobacco company seedbed of Peru S. A. Under completely randomized block design (DCA} with 15 treatments, including the control without pesticides, with 4 replications 5 7 pesticide applications (6 fungicides and 1 disinfectant) it was performed. Copper sulfate 1.5 and 3.0 %. Captan and 2.0% or 1.0, metalaxyl + mancozeb 1.5 and 3.0% or copper oxychloride and 2.0% or 1.0, thiophanate methyl + thiram 1.0 and 2, 0% or fentinacetato 0.75y1.5 °, and quaternary ammonium and 3.5 to 1.75% or all formulated as a commercial product, or to, 8, 16, 24 and 32 days after planting. Evaluated, morphological feature, time of onset, effect of irrigation on the development of algae. Number of algae per cell, incidence of algae in seedling effect of pesticide toxicity to algae and growing, number of seedlings to transplant and economic analysis. From the results it is concluded that seedlings nlcot / ana tabacum l. black variety have a new pathogen that belongs to a species of Spirogyra genus and the best fungicide for control is the commercial mixture of thiophanate fungicides methyl + thiram (Homai% 0% wp) at the dose of 1 and 2 o / oo. while fentinacetato fungicides (80% Brestan pm) and quaternary ammonium they were toxic to snuff seedlings.